Teachers’ Readiness for Integrating Technology in English Language Education: The Roles of Institutional Support, Self-Efficacy, and Technological Competence - Sihombing, Lambok Hermanto; Muliasari, Desiani Natalina; Herlambang, Yusuf Tri; Fadilah, Elly Rizeqia; Supriatna, Nana (Qualitative and Quantitative Research Center, 2025)
The rapid digital transformation in English Language Education (ELE) has made teacher readiness a critical determinant of successful technology integration. This study aims to investigate the roles of institutional support, self-efficacy, and technological competence in shaping teachers’ readiness across two distinct educational landscapes: Australia and Indonesia. Adopting a quantitative research design, data were collected from 125 English language teachers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that institutional support, self-efficacy, and technological competence all exert a positive and significant influence on teacher readiness, collectively explaining 65.8% of the model’s variance (R2=0.658). Among the predictors, self-efficacy emerged as the most dominant driver (β=0.428), highlighting the primacy of internal psychological confidence in adopting digital tools. These results underscore that technology integration is a complex socio-technical process requiring a synergistic approach that balances environmental resources with individual psychological resilience. This study contributes to the field of educational technology by providing a robust cross-cultural model, suggesting that professional development must prioritize building digital agency and supportive ecosystems over mere infrastructure procurement to ensure sustainable digital transitions.